Cardiovascular endothelial inflammation by chronic coexposure to lead (Pb) and polycyclic aromatic hydrocarbons from preschool children in an e-waste recycling area. (March 2019) - Zheng, Xiangbin; Huo, Xia; Zhang, Yu; Wang, Qihua; Zhang, Yuling; Xu, Xijin
Abstract: Lead (Pb) and polycyclic aromatic hydrocarbon (PAH) exposure is positively associated with cardiovascular disease (CVD), and the possible potential mechanism may be caused by damage to the endothelium by modulation of inflammatory processes. No comprehensive research shows co-exposure of Pb and PAH on cardiovascular endothelial inflammation in electronic waste (e-waste) exposed populations. Given this, the aim of this study is to provide evidence for a relationship between Pb and PAH co-exposure and cardiovascular endothelial inflammation, in an e-waste-exposed population, to delineate the link between a potential mechanism for CVD and environmental exposure. We recruited 203 preschool children (3–7 years) were enrolled from Guiyu (e-waste-exposed group, n = 105) and Haojiang (reference group, n = 98). Blood Pb levels and urinary PAH metabolites were measured. Percentages of T cells, CD4 + T cells and CD8 + T cells, complete blood counts, endothelial inflammation biomarker (serum S100A8/A9), and other inflammatory biomarkers [serum interleukin (IL)-6, IL-12p70, gamma interferon-inducible protein 10 (IP-10)] levels were evaluated. Blood Pb, total urinary hydroxylated PAH (ΣOHPAH), total hydroxynaphthalene (ΣOHNap) and total hydroxyfluorene (ΣOHFlu) levels, S100A8/A9, IL-6, IL-12p70 and IP-10 concentrations, absolute counts of monocytes, neutrophils, and leukocytes, as well as CD4 + T cell percentages were significantly higher in exposed children. Elevated blood Pb, urinary 2-hydroxynaphthalene (2-OHNap) and ΣOHFlu levels were associated with higher levels of IL-6, IL-12p70, IP-10, CD4 + T cell percentages, neutrophil and monocyte counts. Mediator models indicated that neutrophils exert the significant mediation effect on the relationship between blood Pb levels and S100A8/A9. IL-6 exerts a significant mediation effect on the relationship between blood Pb levels and IP-10, as well as the relationship between urinary ΣOHFlu levels and IP-10. Our results indicate that children with elevated exposure levels of Pb and PAHs have exacerbated vascular endothelial inflammation, which may indicate future CVD risk in e-waste recycling areas. Graphical abstract: Image 1 Highlights: Pb and PAH toxicity impair inflammatory cells and vascular endothelium. Children from e-waste areas exhibit higher blood Pb and urinary PAH levels. Blood Pb and urinary PAH levels positively correlate with inflammatory biomarkers. Inflammatory biomarker levels may indicate future cardiovascular disease risk. Abstract : E-waste-exposed children have elevated levels of inflammatory biomarkers associated with increased blood Pb levels and urinary PAH metabolites, which may indicate future cardiovascular disease risk.